Hidrologia de bacia de cabeceira com eucaliptocultura e campo nativo na região da campanha gaúcha - Baumhardt, Edner (2014)
The path for the application of the concept sustainable forest management is connected with the proper understanding of the interaction of the planted forest with all other elements of the ecosystem, such as the energy flow, hydrological cycle and the nutrient cycling. However, the studies which elucidate the water yield in a small watershed under the effect of silviculture are in some cases, divergent. This points up a challenge: what is the real effect of the Eucalyptus forest under the hydrological regime of a small watershed in the campanha gaúcha region? Considering that, the purpose of this research is to evaluate the influence of the land use on some parameters of the surface hydrological regime and groundwater. Two small watershed of the city of Rosário do Sul RS were used for the experiment, one of them reforested (MF) with the species of the genus Eucalyptus in 95 ha and the other one (testimony) with natural grassland (MC) in 21 ha. Both small watershed were located in a characteristic Pampa Biome region. In particular, the purposes were: to evaluate the impact of the soil use on the runoff, to quantify the groundwater recharge in unconfined aquifer, to perform the surface and subsurface water balance of the watersheds and to try to obtain an approximate value of the daily use of Eucalyptus under the conditions of the research. Thus, the aim was to monitoring all crucial parameters for a good understanding of the relations and changes involved in a watershed with forest cover and another one with native grassland, like precipitation, interception, runoff and direct recharge of the unconfined aquifer. The surface monitoring began in October 2008 and the subsurface in August 2009, through hydrometric stations and piezometers, properly instrumentalized. The main results were a reduction of 49,8% of the runoff of MF in relation to MC. The MF presented higher direct recharge to groundwater compared to MC. There was also a difference in the underground storage during the period of this study, considering that MF elapsed in a monthly average loss of 1,05 mm at the water table fluctuation. In addition, for the conditions of the research, the MF presented a daily average evapotranspiration of approximately 18,5 Liters/day/water for a space of 6 m2, and this would represent the approximate value of the use of water by a 7 years old eucalyptus tree.